MANAJEMEN KELAS GURU DI SDN 2 SAWAH LAMA DALAM MENCIPTAKAN LINGKUNGAN BELAJAR KONDUSIF - Arin Arianingsih; Ela Kurnia Wati; Pebriyanti Fatonah; Muhammad Kaulan Karima (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Classroom management is a fundamental aspect that determines the effective implementation of the learning process. This study aims to comprehensively describe the classroom management practices applied by teachers at SDN 2 Sawah Lama in an effort to create a conducive learning environment. The research uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews, direct observation of learning activities, and analysis of documentation including classroom photos, class rules, learning schedules, student attendance, and teaching planning documents. The research informants consisted of the principal, classroom teachers, and fourth-grade students. The results of the study show that teachers apply classroom management strategies that include flexible classroom layout, reinforcement of classroom rules at the beginning of the lesson, use of positive reinforcement through rewards, and application of proportional consequences. Teachers also use signals or sound codes to control situations when the classroom becomes noisy, which has proven effective in restoring students' focus in a short time. Teacher-student interactions were positive, characterized by the use of friendly language, ample opportunities to ask questions, and attention to students' emotional comfort. Observations showed that the classroom atmosphere was generally orderly, although there were occasional increases in noise during group activities. Overall, this study confirms that successful classroom management is not only determined by teachers' pedagogical skills, but also supported by consistent school policies and an adequate physical environment. These findings can be used as a reference for teachers and schools in improving learning effectiveness through strengthening classroom management practices.